Разработка учебного стенда по исследованию поляризационных эффектов - Маслов, Н. А.; Галат, А. Б. (ХНУРЕ, 2019)
The article describes the role of polarization effects in human life, as well as a training stand for studying these effects. This stand contains a fairly wide range of diffusing and reflecting plates, polaroids, radiation sources, which allows you to qualitatively study the phenomenon.
Keywords: Разработка учебного стенда; поляризационный эффект